2014
DOI: 10.1186/s12989-014-0044-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability, distribution and clearance of tracheally-instilled and gavaged uncoated or silica-coated zinc oxide nanoparticles

Abstract: BackgroundNanoparticle pharmacokinetics and biological effects are influenced by several factors. We assessed the effects of amorphous SiO2 coating on the pharmacokinetics of zinc oxide nanoparticles (ZnO NPs) following intratracheal (IT) instillation and gavage in rats.MethodsUncoated and SiO2-coated ZnO NPs were neutron-activated and IT-instilled at 1 mg/kg or gavaged at 5 mg/kg. Rats were followed over 28 days post-IT, and over 7 days post-gavage. Tissue samples were analyzed for 65Zn radioactivity. Pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 79 publications
(86 reference statements)
0
53
1
Order By: Relevance
“…As an example, amorphous silica seems to dissolve in tissues over time . Additionally, dissolution of ZnO NMs might be important for their rapid distribution from the lung (Konduru et al 2014) and slow uptake on the skin (Osmond-McLeod et al 2014). Cadmium-based QDs and Ag are examples of NMs that are likely to be oxidised in physiological environments ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As an example, amorphous silica seems to dissolve in tissues over time . Additionally, dissolution of ZnO NMs might be important for their rapid distribution from the lung (Konduru et al 2014) and slow uptake on the skin (Osmond-McLeod et al 2014). Cadmium-based QDs and Ag are examples of NMs that are likely to be oxidised in physiological environments ).…”
Section: Discussionmentioning
confidence: 98%
“…Finally, the faecal excretion in the gavaged rats was higher than in IT instilled rats. For both IT instillation and gavage administration, SiO 2 coating enhanced transport of Zn to thoracic lymph nodes and decreased transport to the skeletal muscle, leading the authors to conclude that coating of NMs may alter the tissue distribution of Zn NMs in some extra-pulmonary tissues (Konduru et al 2014).…”
Section: Multiple Exposure Route Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Even though increased levels of Zn 2+ were found to be associated with in vivo tissues, the source of these ions (ZnO NPs or ZnCl 2 ) did not seem to influence their biodistribution after intraperitoneal injection [82]. Konduru and coworkers demonstrated that upon intratracheal instillation of 65 ZnO NPs in rats, the clearance of 65 Zn was rapid, with only 16-18% of the dose remaining after 2 days, 1.9% after a week and almost none by the end of the 28-day study period [83]. Similarly, inhalation of ZnO NP leads to an increase in Zn 2+ ions in the BALF of exposed animals, although this increase was not long lasting and the Zn levels returned to basal levels within few weeks [72].…”
Section: Zno Np-mediated Cytotoxicity and Inflammatory Responses In Animentioning
confidence: 92%
“…Nano-enabled thermoplastics or nanocomposites can contain nanofillers such as silica nanoparticles (Stojanović et al , 2013), clays (Fang et al , 2008), metal oxides (Perkgoz et al , 2011), carbon fibers (Al-Saleh et al , 2013) and carbon nanotubes (Sahoo et al , 2010) enabling extensive mechanical and electrical properties. Although, ENMs afford many useful properties, certain ENMs can cause adverse health effects such as cytotoxicity (DeLoid et al , 2016; DeLoid et al , 2014; Pirela et al , 2013; Pirela et al , 2014a), genotoxicity (Watson et al , 2013), epigenetic changes (Lu et al , 2016a; Lu et al , 2016b), and lung inflammation upon exposure (Borm et al , 2006; Konduru et al , 2014; Pirela, et al, 2013; Pirela et al , 2016). With this in mind, considerable concern over the hazards that may ensue due to the release of ENMs during consumer use and disposal of nano-enabled thermoplastics has created efforts to understand potential exposures across the life cycle of nano-enabled products (Bouillard et al , 2013; Grassian et al , 2016; Pirela et al , 2014b; Sisler et al , 2014; Wohlleben et al , 2011; Wohlleben and Neubauer, 2016).…”
Section: Introductionmentioning
confidence: 99%